2009
DOI: 10.1159/000264684
|View full text |Cite
|
Sign up to set email alerts
|

Association between Caries Experience and Body Mass Index in 12-Year-Old French Children

Abstract: The prevalence of overweight and obesity reached 19.7% in 12-year-old French children in the year 2005. Recently, nationwide programs have been broadly implemented in France to reduce the overconsumption of sugars, salt and fat. The aims of this study were to assess the distribution of body mass index (BMI) and D3+4MFT index in a sample of 12-year-old French children, and to compare several regression models in order to analyze the association between these two indices. A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 32 publications
7
50
2
6
Order By: Relevance
“…caries in the deciduous dentition. Other studies could not find any association between body weight and prevalence of caries 18,19 either, which agrees with our findings. On the other hand, other findings showed that obese individuals had more carious surfaces than those with normal weight 20 .…”
Section: Discussionsupporting
confidence: 92%
“…caries in the deciduous dentition. Other studies could not find any association between body weight and prevalence of caries 18,19 either, which agrees with our findings. On the other hand, other findings showed that obese individuals had more carious surfaces than those with normal weight 20 .…”
Section: Discussionsupporting
confidence: 92%
“…39 Moreover, in early childhood there is greater parental control over food intake and oral hygiene practices, which can mean lower prevalence of both diseases. 39 The opposite is also true.…”
Section: Discussionmentioning
confidence: 99%
“…39 Moreover, in early childhood there is greater parental control over food intake and oral hygiene practices, which can mean lower prevalence of both diseases. 39 The opposite is also true. Parents that do not perform preventive oral health behaviors and food control, especially regarding the sugar consumption, increase the chances of caries in the primary dentition, and later in the permanent dentition, concomitantly with the presence of obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations